تطوير أداء الجامعات العربية في ظل تطبيق التعلم الإلكتروني: متطلبات وأفاق مع الإشارة لتجربتي مصر والسعودية - عسلي، نور الدين Asali, Nouruldin; العتيبي، راشد بن غازي الهويل (جامعة بني سويف - كلية الآداب بالتعاون مع اتحاد الجامعات العربية, 2020)
تسعى الجامعات في الوطن العربي إلى رفع مستوى أدائها باستغلال كل موارد البيئة الداخلية المتاحة وفق استراتيجية تعمل على ترقية جودة مخرجاتها التعليمية والبحثية، وفي ظل بيئة خارجية تتسم بتزايد التغيرات المتسارعة لتكنولوجيا الإعلام والاتصال، فإن الأمر أصبح يمثل التحدي الأصعب في المواجهة. وبالنظر إلى الجامعات العالمية وتحليل تجاربها فان التعلم الإلكتروني هو أحد أهم الطرق الحديثة التي اعتمدتها الجامعات العالمية من أجل رفع مستوى أدائها وترقية مستواها في الترتيب العالمي، إن تطوير أداء الجامعات العربية يتطلب تحليل استراتيجي للبيئة التي تعمل بها وإلى تبني استراتيجية التعلم الإلكتروني وتهيئة أطراف العملية التعليمية لممارسة التعلم الإلكتروني والاستفادة منه لأقصى حد ممكن. من خلال هذه المداخلة سوف نتطرق إلى مدى إسهام تطبيق التعلم الإلكتروني في تطوير أداء الجامعات العربية بتوافر المتطلبات لتطبيق التعلم الإلكتروني والإشارة لتجربتي مصر والسعودية في هذا الميدان
Universities in the Arab world are seeking to improve their performance by exploiting all available internal environment resources in a strategy that promotes the quality of their educational and research outputs. In an external environment characterized by rapid changes in information and communication technology, this is the most difficult challenge in the confrontation. In view of the international universities and the analysis of their experiences, e-learning is one of the most modern methods adopted by international universities in order to raise the level of their performance and upgrade their level in the world ranking. The development of the performance of Arab universities requires a strategic analysis of the environment in which they work and to adopt an e-learning strategy and prepare the parties to the educational process to practice e-learning and make use of it to the fullest extent possible. Through this article, we will discuss the extent to which the application of e-learning in the development of the performance of Arab universities, the availability of requirements for the application of e-learning and reference to the experiences of Egypt and Saudi Arabia in this field.
Keywords: التعلم الإلكتروني -- الجامعات العربية -- تطوير التعليم -- التجارب العربية